2002
DOI: 10.1074/jbc.m204079200
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Regulation of the Mitochondrial Glycerol-3-phosphate Dehydrogenase by the External NADH Dehydrogenase in Saccharomyces cerevisiae

Abstract: In the yeast Saccharomyces cerevisiae, the two most important systems for conveying excess cytosolic NADH to the mitochondrial respiratory chain are external NADH dehydrogenase (Nde1p/Nde2p) and the glycerol-3-phosphate dehydrogenase shuttle. In the latter system, NADH is oxidized to NAD؉ and dihydroxyacetone phosphate is reduced to glycerol 3-phosphate by the cytosolic Gpd1p; glycerol 3-phosphate gives two electrons to the respiratory chain via mitochondrial glycerol-3-phosphate dehydrogenase (Gut2p)-regenera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 22 publications
0
29
0
1
Order By: Relevance
“…15 Alternatively, cytosolic NADH can be oxidized by the respiratory chain via the glycerol-3-phosphate shuttle, which consists of cytosolic NADH-linked glycerol-3-phosphate dehydrogenase and a membrane-bound glycerol-3-phosphate : ubiquinone oxido-reductase. 150 Furthermore, aerobic growth with D-and L-lactate as carbon source is also permitted via the inducible D,Llactate dehydrogenases localized on the external face of the inner mitochondrial membrane. 46 …”
mentioning
confidence: 99%
“…15 Alternatively, cytosolic NADH can be oxidized by the respiratory chain via the glycerol-3-phosphate shuttle, which consists of cytosolic NADH-linked glycerol-3-phosphate dehydrogenase and a membrane-bound glycerol-3-phosphate : ubiquinone oxido-reductase. 150 Furthermore, aerobic growth with D-and L-lactate as carbon source is also permitted via the inducible D,Llactate dehydrogenases localized on the external face of the inner mitochondrial membrane. 46 …”
mentioning
confidence: 99%
“…1). In addition, Gut2p has been demonstrated to work in a complex together with Nde1p/Nde2p and its activity seems to be strongly inhibited by the activity of these external NADH dehydrogenases [20,24]. This fact implicates that the catalytic role of Gut2p could be insufficient in promoting growth on glycerol under specific conditions, like those occurring during growth on synthetic medium, in which the synthesis of amino acids results in an excess of NADH production.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, we have shown that the activation of NADH dehydrogenase inhibits the Gut2p in such a manner that, at a saturating concentration of NADH, glycerol 3-phosphate is not used as a respiratory substrate. This effect is not a consequence of a direct action of NADH on Gut2p activity because both NADH dehydrogenase and its substrate are needed for Gut2p inhibition (10).…”
mentioning
confidence: 99%
“…The Nde1p/Nde2p system, which is localized in the inner mitochondrial membrane with the catalytic sites projecting toward the intermembrane space, has been shown to directly oxidize cytosolic NADH (7,8). The glycerol 3-phosphate shuttle system, which involves the FADdependent Gut2p (10), is situated in the inner membrane of the mitochondria with the catalytic site projecting toward the cytosol and has been shown to be active in maintaining a cytosolic redox balance (9). In this system, the co-factor NADH is oxidized to NAD ϩ by the cytosolic glycerol-3-phosphate dehydrogenase (Gpd1p) when catalyzing the reduction of dihydroxyacetone phosphate (DHAP) 1 to glycerol 3-phosphate.…”
mentioning
confidence: 99%